Glass fibre reinforced polymer composites toughened with acrylonitrile butadiene nanorubber. (1st March 2016) - Ozdemir, Nazli G.; Zhang, Tao; Hadavinia, Homayoun; Aspin, Ian; Scarpa, Fabrizio
Abstract: We present the effects of nano carboxylic acrylonitrile butadiene (CNBR-NP) and nano acrylonitrile butadiene (NBR-NP) rubbers on the interlaminar shear strength, fracture toughness and Charpy impact strength of glass fibre/dicyandiamide-cured epoxy matrix composites (GFRP). Dispersions of 20 phr of nanorubber into the matrix significantly improved the Mode I (GIC ) and Mode II (GIIC ) delamination fracture toughness of the GFRP panels by 190% and 70% respectively. No noticeable change in the glass transition temperature of the composite panels was observed. Scanning electron microscopy images of the fracture surfaces showed evidence of the existence of toughening mechanisms such as de-bonding of the nanorubber, as well as presence of crack path deflections and fibres bridging.